Overcoming imposter syndrome: the adventures of two new instruction librarians. Issue 3 (1st August 2019) - Martinez, Jessica; Forrey, Meredith
Abstract : Purpose: New librarians rarely feel fully prepared for academic library instruction. This could be attributed to many factors in both Master of Library and Information Science programs and work environments. Imposter syndrome or imposter phenomenon is a common way this insecurity manifests. Imposter phenomenon, first defined in 1978, is an individual's feeling that they will be exposed as a fraud, regardless of how qualified or knowledgeable they actually are. Throughout the first year as new instruction librarians, the authors tracked their experiences with instruction and the imposter phenomenon. This paper aims to illuminate how imposter phenomenon impacts library instruction, provide suggestions for individual librarians and identify what academic libraries can do institutionally to mitigate feelings of fraudulence among their employees. Design/methodology/approach: This paper outlines the history and symptoms of imposter phenomenon, focusing on its presence in libraries. The authors draw on existing literature in psychology and library science, their own experience and a survey of 172 librarians. Suggestions for best practices for easing imposter phenomenon are then discussed based on the experiences of the authors and survey respondents. Findings: This paper suggests several ways to ease the feelings of imposter phenomenon among those employed in academic libraries. Research limitations/implications: This paper is based on the authors' experiences, as well as a survey of 172 librarians. The survey was self-selecting, so the results may be skewed, but the themes apparent throughout the responses indicate that imposter phenomenon in libraries is pervasive and warrants further research. Practical implications: The recommendations presented in this paper will provide new librarians and library administrators with concrete ways to identify and ameliorate imposter phenomenon among new instruction librarians. Originality/value: Though imposter phenomenon has gained popular attention in wider society, extant research has not sufficiently addressed its role in the realm of academic library instruction. Given that most MLIS programs focus on theory rather than practice, finding ways to give new instruction librarians confidence in their positions is an area of research that warrants more exploration.